Cleaning and sputtering using planar acoustoplasma magnetron - Abrahamyan A. S.; Mkrtchyan A. H.; Nalbandyan V. V.; Hovhannisyan N. T.; Chilingaryan R. Yu.; Hakobyan A. S.; Mossoyan P. H. (2018, 2018)
Title screen